UNEMPLOYMENT PERIOD QUANTITATIVE APPROACH THROUGH INFINITE SERVERS QUEUE SYSTEMS - Ferreira, M. A. M.; Filipe, J. A.; Coelho, M. (International Scientific Conference on Quantitative Methods in Economics - Multiple Criteria Decision Making XVIII, 2016)
This paper stands over the (Ferreira, Filipe and Coelho, 2014) work. There using results on the infinite servers queue systems with Poisson arrivals - M|G|? queues - busy period, it is presented an application of those queue systems in the unemployment periods time length parameters and distribution function study. It is now completed with an economic analysis aiming the evaluation of the assistance costs due. These queue systems are adequate to the study of many population processes, and this quality is brought in here. The results presented are mainly on unemployment periods length and their number in a certain time interval. Also, some questions regarding the practical applications of the outlined formulas are discussed.